Preloading Piezoelectric Stack Actuators in High-Speed Nanopositioning Systems - Yong, Yuen Kuan (Frontiers in Mechanical Engineering, 2016)
Recent development in high-speed nanotechnology applications such as scanning probe microscopy and nanofabrication has increased interest on the advancement of high-bandwidth flexure-guided nanopositioning systems. These systems are capable of providing motions with sub-nanometer resolution over a positioning bandwidth of a few kilohertz or more. High-speed nanopositioning devices are commonly driven by compact and stiff piezoelectric stack actuators. However, these actuators are highly sensitive to tensile and lateral forces. During high-speed operations, excessive inertia force due to the effective mass of nanopositioning system could potentially damage the actuator. To protect the piezoelectric actuator, preload is often applied to compensate for these inertial forces. This article surveys key challenges in existing preload techniques in the context of high-speed nanopositioning designs, and explores how these challenges can be overcome.